Penerapan Model PjBL untuk Meningkatkan Kemampuan Berpikir Kritis di Era Merdeka Belajar - Riasty, Ageng; Sari, Dhany Efita (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
In the era of the independent learning curriculum, critical thinking skills are very important in facing increasingly fierce competition. One learning approach that aims to develop students’ critical thinking skill is IPAS learning. One of the effective learning models to improve students’critical thinking skills in IPAS learning is the Project Based Learning (PjBL) model. The research uses Classroom Action Research method which consists of pre-cycle, cycle I, and cycle II. The purpose of this study was to evaluate students’ critical thinking skills which were still low, as identified in the pre-cycle activities. The research subjects consisted of 16 4th grade students, with 10 male students and 6 female students. The data collection technique used was non-test, using questionnaires and observation sheets. The results showed an increase in the level of students’ critical thinking skills each cycle. This confirms that the use o the PjBL model is effective in improving students’ critical thinking skills in learning IPAS in elementary schools.